Implementing enterprise risk management from methods to applications - Lam, James (Hoboken, New Jersey Wiley, 2017)
Enterprise risk management (ERM) is a complex yet critical issue that all companies must deal with in the twenty-first century. Failure to properly manage risk continues to plague corporations around the world. ERM empowers risk professionals to balance risks with rewards and balance people with processes.But to master the numerous aspects of enterprise risk management, you must integrate it into the culture and operations of the business. No one knows this better than risk management expert James Lam, and now, with Implementing Enterprise Risk Management: From Methods to Applications, he distills more than thirty years' worth of experience in the field to give risk professionals a clear understanding of how to implement an enterprise risk management program for every business. -- Provided by publisher.
Preface -- Acknowledgments -- Part One ERM in Context -- Chapter 1 Fundamental Concepts and Current State -- Chapter 2 Key Trends and Developments -- Chapter 3 Performance-Based Continuous ERM -- Chapter 4 Stakeholder Requirements -- Part Two Implementing an ERM Program -- Chapter 5 The ERM Project -- Chapter 6 Risk Culture -- Chapter 7 The ERM Framework -- Part Three Governance Structure and Policies -- Chapter 8 The Three Lines of Defense -- Chapter 9 Role of the Board -- Chapter 10 The View from the Risk Chair -- Chapter 11 Rise of the CRO -- Chapter 12 Risk Appetite Statement -- Part Four Risk Assessment and Quantification -- Chapter 13 Risk Control Self-Assessments -- Chapter 14 Risk Quantification Models -- Part Five Risk Management -- Chapter 15 Strategic Risk Management -- Chapter 16 Risk-Based Performance Management -- Part Six Risk Monitoring and Reporting -- Chapter 17 Integration of KPIs and KRIs -- Chapter 18 ERM Dashboard Reporting --- Chapter 19 Feedback Loops -- Part Seven Other ERM Resources -- Chapter 20 Additional ERM Templates and Outlines -- Index
Includes index.
Keywords: Risk management